Cerebral Perfusion Pressure in Traumatic Brain Injury: A Dynamic Battlefield of Flow and Pressure - Primanov, Rama Mahardika; Putri Maharani, Dinda; Maria Situmorang, Ruth; Indharty, R. R. Suzy; Marolop Pangihutan, Andre (Jurnal Neuroanestesi Indonesia, 2026)
Introduction: Traumatic brain injury (TBI) affects 27-69 million people annually, with over 55 million living with long-term disability. A major management challenge is disruption of cerebral autoregulation, a mechanism that maintains stable cerebral blood flow (CBF) despite systemic pressure changes. Impaired cerebral perfusion pressure (CPP) autoregulation promotes ischemia, edema, and metabolic imbalance, worsening neurological outcomes. Method: This narrative review synthesized literature from PubMed, Google Scholar, ScienceDirect, and the Cochrane Library, focusing on studies from the past decade. Keywords included “cerebral perfusion pressure,” “autoregulation,” “traumatic brain injury,” “TBI,” “mechanism,” “pressure reactivity index,” and “monitoring.” Discussion: TBI-related autoregulation impairment stems from vascular injury, inflammation, and myogenic dysfunction, with patterns ranging from intact to delayed or absent responses. The pressure reactivity index (PRx) enables continuous autoregulation assessment and determination of patient-specific optimal CPP (CPPopt). Observational data link maintaining CPP near CPPopt with better outcomes, while time below CPPopt increases mortality risk. Experimental models identify endothelin-1, ERK1/2, and interleukin-6 as key mediators, with targeted interventions showing potential to preserve reactivity. Conclusion: Integrating mechanistic insights with invasive monitoring and PRx-guided CPP optimization offers a promising, individualized strategy for TBI care, warranting confirmation in large clinical trials.